Computer techniques in power system analysis : 3e - Pai, Dr. M A.; Chatterjee, Dr. Dheeman ([S.l.] : McGraw Hill Education (India) Private Limited, 2014)
Meant for the undergraduate students of Electrical Engineering, this book carefully and diligently covers all the aspects related to the teaching of Computer Techniques in Power System Analysis. Emphasis is given on computer techniques and software tools along with inclusion of new modern topics such as HVDC FACTS, ELD and WP that explains the underlying concepts lucidly and rigorously showing students how computer applications yield more insight into system behavior than is possible by manual calculations.